Islamization Under President Zia: Shaping Pakistani Society in the Zia-ul-Haq Era - Khalid, Muhammad (Al-Basirah Journal, 2025)
Due to the political crisis in Pakistan, General Zia-ul-Haq's Martial Law regime assumed power on July 5, 1977. The period from 1977 to 1988, under Zia-ul-Haq's leadership, witnessed a significant intensification of the Islamization process. During this time, he implemented a comprehensive initiative aimed at eliminating non-Islamic practices within the Pakistani state and society. The Islamization of Pakistani society during President Zia-ul-Haq's regime marked a significant and transformative period in the country's history. From 1977 to 1988, President Zia implemented a series of policies aimed at embedding Islamic principles in various facets of Pakistani life, including politics, education, and law. This intentional shift towards a more Islamic governance model had profound and lasting effects on the nation's social fabric. This paper delves into the key initiatives and strategies employed by President Zia to Islamize Pakistan, exploring the motivations behind these measures and their impact on the nation's cultural, political, and legal landscape. President Zia's Islamization policies, ostensibly designed to transform Pakistan into an Islamic state, involved legal and educational changes. The introduction of Islamic laws, such as the Hudood Ordinances, aimed to align the legal system with religious principles. However, critics argued that these policies were primarily a tool for President Zia to legitimize and strengthen his political power by garnering support from conservative religious segments of society. The measures faced criticism for potential marginalization of certain groups and raising concerns about the genuine commitment to creating an inclusive society.